City residence prepare towards implementation local lane of non-motorized in Kangar, Perlis. - Nur Afiza Azura Bt M Najimudin (School of Environmental Engineering, University Malaysia Perlis, 2014)
An effective plan needs to be done in order to encourage city residences to use non-motorized vehicles in the city to address the problem of congestion, delay and air pollution that arose. The implementation of non-motorized lane can be done if the major factors that affect the use of non-motorized transportation are identified. City residences have the big impact towards the implementation of non-motorized lane, so this research was conducted to investigate the level of satisfaction of city residence towards this implementation whether it is suitable or not to implement in this city.